Utilidad clínica de los biomarcadores séricos en pacientes con cáncer de ovario. Revisión sistemática - Medina Guamán, Haly Lariza (2024)
The ovarian cancer (OC) is one of the leading carcinogen diseases in women, which records a high mortality rate due to its late diagnosis. Serum biomarkers play a critical role in diagnosing, predicting, monitoring and evaluating treatment response to this disease. The purpose of this paper was to analyse major biomarkers, describe their clinical utility and identify populations at highest risk. To this end, it was conducted a systematic review, using databases such as PubMed, Scopus, Lilacs and Scielo, in accordance with the guidelines of the Cochrane system. During the screening process, the PRISMA method was used to select publications dating from 2014. The systematic review includes 10 articles that were assessed using JBI tools, which showed a low risk of bias. The most commonly used biomarkers are CA125 and HE4 (80% of studies reviewed), followed by YKL-40, IL-6 and E-CAD. These biomarkers have proven to be useful for the identification of high serous subtypes of CO, the prediction of a possibility of an optimal fat-reducing surgery, the monitoring of the treatment response and the recurrence diagnose. The combination of biomarkers, especially CA125 and HE4, showed higher diagnostic accuracy than when used separately, where the sensitivity level of all biomarkers indicated 52.17% to 93.7% while the specificity was 25.8% to 95.6%. Postmenopausal women were also found to have the highest incidence of CO (59.3%), due to factors such as hormonal changes, genetic mutations and family history. In conclusion, biomarkers such as CA 125, HE4, YKL 40, IL-6 and E-CAD are valuable complementary tools for clinical CO management, supporting the disease diagnosis, prediction and tracking. Yet more research, especially experimental studies, is needed in order to validate these findings and explore combinations of biomarkers to improve the accuracy of their diagnosis and prediction